2002
DOI: 10.1007/s10350-004-6147-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Lymph Node Metastasis in T1 Carcinoma of the Colon and Rectum

Abstract: T1 colorectal carcinomas with lymphovascular invasion, sm3 depth of invasion, and location in the lower third of the rectum have a high risk of lymph node metastasis. These lesions should have an oncologic resection. In a case of the lesion in the lower third of the rectum, local excision plus adjuvant chemoradiation may be an alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
425
10
17

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 645 publications
(476 citation statements)
references
References 33 publications
15
425
10
17
Order By: Relevance
“…The high level of the pT increases the presence of LVI. In addition, Nascimbeni et al also demonstrated that T1 CRC with LVI, sm3 depth of invasion, and location in the lower third of the rectum have a high risk of LMN [13]. Although it was not shown in our study, the site of tumor may increase the LVI.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The high level of the pT increases the presence of LVI. In addition, Nascimbeni et al also demonstrated that T1 CRC with LVI, sm3 depth of invasion, and location in the lower third of the rectum have a high risk of LMN [13]. Although it was not shown in our study, the site of tumor may increase the LVI.…”
Section: Discussioncontrasting
confidence: 60%
“…However, some tumors, although diagnosed in a small size, may already have LNM and even distant metastasis. The incidence of LNM in the submucosal invasive CRC has been reported to be approximately 7-15 %, and the treatment consists of endoscopic polypectomy, local excision for selected patients, or radical resection [12][13][14]. Many series in which long-term follow-up was performed have revealed that the local recurrence rate is high although submucosal invasive CRC can be expected to be treated by local excision without adjuvant therapy [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] When histopathologic examination of tumors removed by endoscopic procedures indicates invasion into the submucosa (T1 colorectal cancer), additional major surgery is recommended because of the risk of lymph node metastasis. 7 The frequency of lymph node metastasis, however, is <15% based on large-scale studies, [8][9][10][11][12][13][14][15] and 85% of T1 colorectal cancer patients are cured by endoscopic treatment alone. The establishment of reliable criteria for discriminating patients with a high risk of lymph node metastasis from those with a low risk is thus an important issue in terms of providing adequate treatment to patients with T1 colorectal cancer.…”
mentioning
confidence: 99%
“…The frequency of lymph node metastases is proportional to the degree of depth being 2, 8, and 23 %, respectively [6]. The Paris classification [3], revised in Kyoto in 2008 [7], defines every lesion extended no more than 1 mm in the submucosal layer as 'sm1'.…”
mentioning
confidence: 99%